The Gesta Guillelmi of William of Poitiers: The Dynamics of a Failed Publication - Lauri Leinonen (Tabularia)
This article explores William of Poitiers’ Gesta Guillelmi for its failed manuscript transmission. In spite of possessing various advantages, literary and social, the work found very few readers and was soon forgotten. It is proposed that the transmission relied on, or consisted of, an untidy autograph, lost in the eighteenth century. According to Orderic Vitalis, William did not complete the work due to “unfavourable circumstances”, probably related to the latter’s connection to the Conqueror. The essay contributes to two burgeoning scholarly discussions, on authorial publishing and on why some works failed to find readers.